Zika Virus: Mechanisms of Infection During Pregnancy. Issue 9 (September 2017) - King, Nicholas J.C.; Teixeira, Mauro M.; Mahalingam, Suresh
Abstract : Immune status changes during pregnancy, with pro-inflammatory and anti-inflammatory contexts at different stages, making pregnant women potentially more susceptible to various infections. Infection by Zika virus during pregnancy can cause developmental damage to the fetus, and the altered immune response during pregnancy could contribute to disease during Zika infection.